PENGARUH KEJELASAN SASARAN ANGGARAN, PENGENDALIAN INTERNAL DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP AKUNTABILITAS KINERJA KELURAHAN DI KECAMATAN RUNGKUT KOTA SURABAYA - Shabrina Salsabila; Tituk Diah Widajantie (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The purpose of this study is to determine the effect of Clearance Of Budget Goals, Internal Control And Quality Of Human Resources On Performance Accountability Of Kelurahan Rungkut This research is a quantitative study with a total of 46 samples. Data collection methods used questioner. Data were analyzed with Partial Least Square. The result of the research showed that variable Internal Control, Quality Of Human Resources affects Performance Accountability with t-statistics > 1.96, Clearance Of Budget Goals has not effect on Performance Accountability and R2 value of model is 0.748 or 74.8%.